2021
DOI: 10.1002/ajmg.a.62183
|View full text |Cite
|
Sign up to set email alerts
|

Confined placental mosaicism involving multiple de novo copy number variants associated with fetal growth restriction: A case report

Abstract: The presence of multiple large (>1 Mb) copy number variants (CNVs) in non‐malignant tissue is rare in human genetics. We present a liveborn male with a birth weight below the first percentile associated with placental mosaicism involving eight 2.4–3.9 Mb de novo duplications. We found that the duplications likely co‐localized to the same cells, were mosaic in the placenta, and impacted maternal and paternal chromosomes. In addition, 27.4 Mb and 240 genes were duplicated in affected cells, including candidate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(33 reference statements)
0
3
1
Order By: Relevance
“…Based on VAF (~0.1 for both Illumina and Nanopore), absence from the parental genomes, and a relatively low level of ZNF407-driven CNDP1 expression as compared to ZNF407, it seems likely that this duplication is somatic. While there are examples of placenta-specific duplications associated with adverse fetal outcomes (Del Gobbo et al 2021), that was not the case with the duplication reported here. However, this does add to evidence that a small minority of somatically acquired mutations affect the placental transcriptome and a subset of these instances may impact fetal development.…”
Section: Genome Variationcontrasting
confidence: 71%
“…Based on VAF (~0.1 for both Illumina and Nanopore), absence from the parental genomes, and a relatively low level of ZNF407-driven CNDP1 expression as compared to ZNF407, it seems likely that this duplication is somatic. While there are examples of placenta-specific duplications associated with adverse fetal outcomes (Del Gobbo et al 2021), that was not the case with the duplication reported here. However, this does add to evidence that a small minority of somatically acquired mutations affect the placental transcriptome and a subset of these instances may impact fetal development.…”
Section: Genome Variationcontrasting
confidence: 71%
“…A case report discovered that a newborn (birth weight < 1 st percentile for GA) was affected by placental mosaicism involving eight de novo duplications of 2.4-3.9 Mb in length of chromosomes 1, 5, 6, 7, 8, and 11. 37 UPD may occur in the placenta as a condition of CPM. If the CMA analysis following amniocentesis for FGR cases were normal, UPD should be considered when the maternal cell-free DNA (cfDNA) sequencing finds a trisomy involving a chromosome of imprinted genes 6, 7, 11, 14, 15, and 20.…”
Section: Confined Placental Mosaicism (Cpm)mentioning
confidence: 99%
“…Mosaicism with CNVs could also disrupt the placental function and cause IUGR. A case report discovered that a newborn (birth weight < 1 st percentile for GA) was affected by placental mosaicism involving eight de novo duplications of 2.4–3.9 Mb in length of chromosomes 1, 5, 6, 7, 8, and 11 37 …”
Section: Placental Genetic Etiologies For Fgrmentioning
confidence: 99%
“…These duplications were mosaic, detected not in the whole placenta, but only in its specific regions, and re-engaged both parental chromosomes, indicating a post-zygotic origin. Among the duplicated genes, there were some (including KISS1 and REN ) involved in trophoblast proliferation and angiogenesis and thus important for placental function and fetal growth [ 46 ]. CPM diagnosis not only explains the pathogenesis of FGR, but also ensures significant information for postnatal follow up.…”
Section: Placental Fgr Causesmentioning
confidence: 99%